Anxiety, stress and coping stress strategies in researchers: COVID-19 pandemic - Batista, Patrícia (2022)
Background: The COVID-19 pandemic has affected worldwide, with the need for changes at the level of personal and professional life. The researchers, as with other professions, have been one of the professional classes that have had to reinvent. Aim: This study had the aim, to assess the anxiety, stress, and coping strategies in Portuguese researchers during the COVID-19 pandemic. Methods: Data were collected from 243 researchers using an online questionnaire, that included a Depression, Anxiety and Stress (DASS-21), and Coping Inventory for Stressful Situations (CISS). The study was performed between 1st June to 11th August 2021. Results: The findings suggest singles and younger researchers showed higher values of stress and anxiety. Medical and health sciences research areas presented higher levels on the DASS21 stress scale (p<0.05). Also, the results showed a moderate or moderate strong significant positive linear relationship between the scales (p<0.001): DASS-21 stress and anxiety; CISS21 emotional-oriented with DASS-21 stress and anxiety. Conclusion: The findings of this study support the growing concern for the mental health of the population, and in this case in particular, for the mental health of researchers. This study draws attention to the need for the intervention with more extensive and diverse studies in this professional class.